Self-supporting layered molybdenum copper bifunctional electrode and preparation method and application thereof
Patent Information
- Application Number
- CN202610963765.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-30
- Publication Date
- 2026-10-23
AI Technical Summary
[0005]旨在解决上述常用技术中粘结剂法导致的活性位点降低与稳定性差,以及现有自支撑电极功能单一、无法同步实现还原无机氮产氨与存储氨的技术问题,本发明提供了一种自支撑层状钼铜双功能电极的制备方法,包括步骤:
本发明在基底表面原位电还原共沉积钼铜双金属,并结合煅烧处理,直接获得自支撑结构的双功能电极。该方法无需使用任何高分子粘结剂,避免了传统涂覆工艺中活性位点被包覆、导电性下降及电极稳定性差的问题。所制备的双功能电极中,三氧化钼呈纳米带交织形成的多孔层状结构,为氨的存储提供了丰富的氢键作用位点;氧化亚铜颗粒均匀分布于三氧化钼的层间和表面,赋予电极优异的电催化还原高价态无机氮产氨的活性。两者协同作用,使同一电极同时具备电化学还原高价态无机氮选择性产氨和原位存储回收氨的双重功能,解决了现有技术中还原与回收需分步进行、电极功能单一的技术难题。
Smart Images

Figure CN122959787A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrode preparation technology, specifically relating to a self-supporting layered molybdenum-copper bifunctional electrode, its preparation method, and its application. Background Technology
[0002] Ammonia (NH3), the world's second-largest chemical after sulfuric acid, is widely used in fertilizers, chemical raw materials, and new energy sources. Currently, its production mainly relies on the energy-intensive and greenhouse gas-emitting Haber-Bosch process. Inorganic nitrogen (nitrates, nitrites, nitrogen dioxide, ammonia, etc.), as ubiquitous water and air pollutants, could offer a new pathway to alleviate NH3 production pressures and environmental pollution if converted to NH3 and recovered through electrochemical reactions. However, current methods for electrochemically reducing inorganic nitrogen to NH3 and recovering NH3 use different electrodes, resulting in complex processes, high equipment investment, and the ammonia produced during reduction easily causing secondary pollution.
[0003] To address the challenges in electrode fabrication, researchers typically employ polymeric binders such as polyvinylidene fluoride (PVDF) to adhere catalytic materials to the substrate surface. This method is simple and easy to implement. However, the polymeric binder inevitably coats the catalyst, leading to a reduction in active sites and affecting the conductivity and electron transport rate of the electrode material. Furthermore, the bonding is merely surface adhesion and does not achieve a tight bond between the material and the substrate, resulting in catalyst detachment during long-term operation or under high current density conditions, leading to poor stability. Therefore, compared to binder-based composite electrodes, self-grown (i.e., self-supporting) electrodes have become an important development direction. However, currently reported self-supporting electrodes all possess only a single function; no self-supporting electrode can simultaneously achieve the dual functions of reducing inorganic nitrogen to produce ammonia and storing ammonia.
[0004] Therefore, it is necessary to provide a bifunctional electrode and its preparation method that can avoid the problems of reduced active sites and poor stability caused by the use of binders, and simultaneously realize the electrochemical reduction of inorganic nitrogen to produce ammonia and the in-situ storage of ammonia, so as to solve the technical defects of the separation of reduction and recovery phases and the single function of self-supporting electrodes in the prior art. Summary of the Invention
[0005] To address the issues of reduced active sites and poor stability caused by binder methods in commonly used techniques, and the limitations of existing self-supporting electrodes that offer only single function and cannot simultaneously achieve ammonia production and storage from inorganic nitrogen reduction, this invention provides a method for preparing a self-supporting layered molybdenum-copper bifunctional electrode, comprising the following steps: The substrate was placed in a molybdenum-copper solution for electro-reduction co-deposition, and molybdenum trioxide and cuprous oxide were deposited in situ on the surface of the substrate to obtain the precursor electrode. The precursor electrode is calcined to obtain a bifunctional electrode. In the bifunctional electrode, the molybdenum trioxide is in the form of nanoribbons, and the nanoribbons are interwoven to form a porous layered structure. The cuprous oxide is distributed in the interlayer and / or surface of the molybdenum trioxide in the form of particles.
[0006] Furthermore, the substrate includes at least one of nickel foam, titanium sheet, titanium mesh, nickel sheet, and iron sheet.
[0007] Furthermore, the preparation of the molybdenum-copper solution includes: mixing copper salt and molybdenum salt in a solvent to obtain the molybdenum-copper solution; The copper salt includes at least one of copper sulfate, copper chloride, and copper nitrate, and the molybdenum salt includes at least one of sodium molybdate, potassium molybdate, and ammonium molybdate.
[0008] Furthermore, the concentration of copper in the molybdenum-copper solution is 10-150 mg / L, and the concentration of molybdenum is 1000-9000 mg / L; The molar ratio of molybdenum to copper in the molybdenum-copper solution is 4.5-600.
[0009] Furthermore, the current density of the electroreduction co-deposition is 1-50 mA / cm². 2 The duration is 10-300 minutes.
[0010] Furthermore, the calcination treatment is carried out at a temperature of 200-500℃ for a duration of 60-200 min.
[0011] This invention provides a self-supporting layered molybdenum-copper bifunctional electrode, which is prepared by the preparation method described above. The bifunctional electrode exhibits a porous layered structure with interwoven nanoribbons, comprising layered molybdenum trioxide and granular cuprous oxide, wherein the cuprous oxide is distributed between the layers and / or on the surface of the molybdenum trioxide.
[0012] Furthermore, the mass ratio of molybdenum to copper in the bifunctional electrode is 0.9-1.1:0.9-1.1.
[0013] Furthermore, including: The self-supporting layered molybdenum-copper bifunctional electrode is placed as the working electrode in wastewater containing high-valence inorganic nitrogen. A voltage is applied to the bifunctional electrode, causing the high-valence inorganic nitrogen to undergo an electrochemical reduction reaction on the surface of the bifunctional electrode to generate ammonia. At the same time, the generated ammonia is stored in situ on the electrode by utilizing the hydrogen bonding between the layered structure of molybdenum trioxide in the bifunctional electrode and ammonia.
[0014] Furthermore, the high-valence inorganic nitrogen includes at least one of nitrate, nitrite, nitric oxide, and nitrogen dioxide, with a concentration of 20-500 mg N / L; the applied voltage is 1-8 V, and the reaction time is 2-10 h.
[0015] Compared with the prior art, the present invention has at least the following advantages: This invention involves in-situ electroreduction co-deposition of a molybdenum-copper bimetallic compound on a substrate surface, followed by calcination, to directly obtain a self-supporting bifunctional electrode. This method eliminates the need for any polymer binders, avoiding the problems of active sites being coated, reduced conductivity, and poor electrode stability associated with traditional coating processes. In the prepared bifunctional electrode, molybdenum trioxide exhibits a porous layered structure formed by interwoven nanoribbons, providing abundant hydrogen bonding sites for ammonia storage. Cuprous oxide particles are uniformly distributed between the layers and on the surface of the molybdenum trioxide, endowing the electrode with excellent electrocatalytic activity for the electrocatalytic reduction of high-valence inorganic nitrogen to ammonia. The synergistic effect of these two components enables the same electrode to simultaneously possess the dual functions of selectively producing ammonia from high-valence inorganic nitrogen through electrochemical reduction and in-situ storage and recovery of ammonia, solving the technical challenges of separate reduction and recovery processes and the single-function electrode in existing technologies. Attached Figure Description
[0016] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.
[0017] Figure 1 This is a scanning electron microscope image of sample one in Example 1 of the present invention; Figure 2 This is a scanning electron microscope image of sample two in Example 1 of the present invention; Figure 3 The transmission electron microscope and energy dispersive spectroscopy (EDS) spectra of sample two in Example 1 of this invention are shown below. Figure 4 These are the FTIR analysis images of samples two, three, and four in Example 1 of this invention; Figure 5 The diagram shows the effect of electrochemical reduction of nitrate to ammonia production in samples two, three, and four in Example 1 of this invention. Figure 6 This is a diagram showing the effect of electrochemical reduction of nitrite to produce ammonia in samples two, three, and four in Example 1 of this invention; Figure 7 This is a graph showing the effect of electrochemical reduction of nitrogen dioxide to produce ammonia in samples two, three, and four in Example 1 of this invention; Figure 8The diagram shows the effect of electrochemical storage of ammonia, sodium, and potassium in samples two, three, and four in Example 1 of this invention. Figure 9 The figure shows the results of the cycle stability test of sample 2 in Experiment 7 of Embodiment 1 of the present invention. Detailed Implementation
[0018] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0019] Furthermore, the technical solutions of the various embodiments of the present invention can be combined with each other, but only if they are based on the ability of those skilled in the art to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such combination of technical solutions does not exist and is not within the scope of protection claimed by the present invention.
[0020] When numerical ranges are given in the embodiments, it should be understood that, unless otherwise stated in the present invention, both endpoints of each numerical range and any value between the two endpoints may be selected. Unless otherwise defined, all technical and scientific terms used in this invention, as well as the prior art known to those skilled in the art and the description of the invention, may be implemented using any prior art methods, devices, and materials similar to or equivalent to the methods, devices, and materials in the embodiments of the present invention.
[0021] This invention provides a method for preparing a self-supporting layered molybdenum-copper bifunctional electrode, comprising the following steps: S1. The substrate is placed in a molybdenum-copper solution for electroreduction co-deposition, and molybdenum trioxide and cuprous oxide are deposited in situ on the surface of the substrate to obtain the precursor electrode.
[0022] In some embodiments, the substrate includes at least one of nickel foam, titanium sheet, titanium mesh, nickel sheet, and iron sheet.
[0023] In some embodiments, the preparation of the molybdenum-copper solution includes: mixing copper salt and molybdenum salt in a solvent to obtain the molybdenum-copper solution; The copper salt includes at least one of copper sulfate, copper chloride, and copper nitrate, and the molybdenum salt includes at least one of sodium molybdate, potassium molybdate, and ammonium molybdate.
[0024] In some embodiments, the concentration of copper in the molybdenum-copper solution is 10-150 mg / L, and the concentration of molybdenum is 1000-9000 mg / L; the molar ratio of molybdenum to copper in the molybdenum-copper solution is 4.5-600.
[0025] For example, the molar ratio of molybdenum to copper in the molybdenum-copper solution can be 40, 50, 90, 100, 200, 500, and any value between these minimum and maximum values, or a range of any two values.
[0026] This invention controls the copper concentration in the molybdenum-copper solution to be 50 mg / L and the molybdenum concentration to be 7000 mg / L, resulting in a near 1:1 mass ratio of molybdenum to copper in the precursor electrode after electroreduction co-deposition. In the bifunctional electrode obtained after calcination, cuprous oxide and molybdenum trioxide form a uniformly distributed and tightly bound composite structure, working synergistically: cuprous oxide provides highly efficient active centers for the electrocatalytic reduction of high-valence inorganic nitrogen to ammonia, while molybdenum trioxide provides abundant ammonia storage sites. When the molybdenum-copper mass ratio is approximately 1:1, the reduction active sites and storage sites achieve the optimal ratio, significantly improving the selectivity for reducing high-valence inorganic nitrogen to ammonia (as shown in the examples, the selectivity for nitrate reduction to ammonia reaches 98.5%, nitrite to 99.9%, and nitrogen dioxide to 98.5%). In contrast, when the molybdenum-copper mass ratio deviates from 1:1 (e.g., excess molybdenum in Comparative Example 3 and excess copper in Comparative Example 4), the ammonia selectivity significantly decreases (to 67.9% and 76.1%, respectively). Meanwhile, this ratio also ensures efficient conversion of high-valence inorganic nitrogen (nitrate removal rate of 98.4% and nitrite removal rate of 99.8%) and high-capacity in-situ storage of ammonia (ammonia recovery rate of 98.7%), avoiding problems such as waste of active sites, insufficient storage capacity and reduced selectivity caused by excessive amount of one phase.
[0027] In some embodiments, the current density of the electroreduction co-deposition is 1-50 mA / cm². 2 The duration is 10-300 minutes.
[0028] For example, the current density of the electroreduction co-deposition can be 1 mA / cm². 2 2 mA / cm 2 5 mA / cm 2 10mA / cm 2 15 mA / cm 2 20 mA / cm 2 25 mA / cm 2 30 mA / cm 2 35 mA / cm 2 40 mA / cm 2 45 mA / cm 2 50mA / cm 2 And each of these minimum and maximum values, or any range of any two values.
[0029] For example, the duration of the electroreduction co-deposition can be 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, 80 min, 100 min, 120 min, 150 min, 180 min, 200 min, 250 min, 300 min, and any value between these minimum and maximum values, or a range of any two values.
[0030] In step S1, the present invention co-deposits molybdate and copper ions on the surface of a substrate material through electrochemical reduction, thereby obtaining a self-supporting Cu2O-MoO3 electrode with high activity and stability in inorganic nitrogen reduction to produce and store NH3, as well as a special nanolayer morphology. It not only avoids catalyst aggregation and has high electrochemical reaction active sites and NH3 storage space, but also forms a self-supporting nanolayer structure.
[0031] Specifically, molybdate and copper ions are co-deposited on the substrate surface, where molybdate is reduced to layered molybdenum trioxide. The initially formed layered molybdenum trioxide gradually grows and eventually forms a thin film of layered molybdenum trioxide in situ on the substrate surface. During the molybdenum trioxide deposition process, copper ions are reduced to cuprous oxide and co-deposited in the layered molybdenum trioxide film. The above materials are then further calcined and crystallized at high temperature to form a self-supporting layered Cu2O-MoO3 electrode.
[0032] S2. The precursor electrode is calcined to obtain a bifunctional electrode; in the bifunctional electrode, the molybdenum trioxide is in the form of nanoribbons, and the nanoribbons are interwoven to form a porous layered structure; the cuprous oxide is distributed in the interlayer and / or surface of the molybdenum trioxide in the form of particles.
[0033] In some embodiments, the calcination treatment is performed at a temperature of 200-500°C for a duration of 60-200 min.
[0034] For example, the calcination temperature can be 200℃, 220℃, 250℃, 280℃, 300℃, 320℃, 350℃, 380℃, 400℃, 420℃, 450℃, 480℃, 500℃, and any value between these minimum and maximum values, or a range of any two values.
[0035] In this invention, a calcination treatment is set at a temperature of 200-500℃ for a duration of 60-200 minutes, the effects of which include: Crystal form regulation and structure stabilization. In the precursor electrodes obtained by electroreduction co-deposition, molybdenum trioxide and cuprous oxide exhibit low crystallinity and irregular lattice arrangement. Heat treatment at 200-500℃ can promote grain growth and crystal form improvement of molybdenum trioxide and cuprous oxide, forming stable crystalline phases (such as…). Figure 3 (as shown in the XRD pattern), thereby enhancing the structural stability of the electrode material in long-term electrochemical reactions.
[0036] Strengthening the bond between the substrate and the active material. During calcination, interfacial diffusion and chemical bonding occur between the metal oxides in the precursor and the substrate (nickel foam, titanium sheets, etc.), transforming the originally physically deposited active layer into a self-supporting structure tightly bonded to the substrate. This further alleviates the problem of catalyst detachment in traditional binder methods, significantly improving the mechanical stability and cycle life of the electrode.
[0037] Remove residual moisture and impurities. The electrodeposition process may introduce small amounts of water of crystallization or unreacted salts. Calcination can effectively remove these impurities, preventing them from interfering with catalytic activity or causing side reactions in electrochemical reactions. At the same time, it further increases the specific surface area and porosity of the electrode, which is beneficial for electrolyte penetration and ammonia diffusion and storage.
[0038] Based on the above, calcination is a key step in transforming the precursor into a bifunctional electrode with excellent crystallinity, strong interfacial bonding, and a porous layered self-supporting structure. It is a guarantee for achieving high activity, high selectivity, and high stability of the electrode.
[0039] This invention provides a self-supporting layered molybdenum-copper bifunctional electrode, which is prepared by the preparation method described above. The bifunctional electrode exhibits a porous layered structure with interwoven nanoribbons, comprising layered molybdenum trioxide and granular cuprous oxide, wherein the cuprous oxide is distributed between the layers and / or on the surface of the molybdenum trioxide.
[0040] In some embodiments, the mass ratio of molybdenum to copper in the bifunctional electrode is 0.9-1.1:0.9-1.1.
[0041] In the bifunctional electrode prepared by this invention, molybdenum trioxide (MoO) is presented as nanoribbons with a width of approximately 8-12 nm. These nanoribbons interweave to form a porous layered structure with nanoscale pores. This structure has the following advantages: First, the porous structure formed by the interweaving of nanoribbons significantly increases the specific surface area of the electrode, providing abundant active sites for electrocatalytic reactions and ample space for ammonia storage. Second, the porous structure facilitates electrolyte penetration and ion transport, shortens the diffusion paths of reactant and product molecules, and improves the kinetic efficiency of the electrochemical reaction. Third, cuprous oxide particles are uniformly distributed between the layers and on the surface of MoO, forming a tight heterogeneous interface, promoting rapid electron transfer between cuprous oxide and MoO, overcoming the poor conductivity of MoO, and reducing the energy consumption of the electrochemical reaction. This self-supporting structure requires no binder, avoiding problems such as active site coating, decreased conductivity, and catalyst detachment in traditional electrode preparation, and significantly improving electrode stability.
[0042] This invention also provides the application of a self-supporting layered molybdenum-copper bifunctional electrode in the reduction of high-valence inorganic nitrogen and the recovery of ammonia, comprising: placing the self-supporting layered molybdenum-copper bifunctional electrode as a working electrode in wastewater containing high-valence inorganic nitrogen, applying a voltage to the bifunctional electrode to cause the high-valence inorganic nitrogen to undergo an electrochemical reduction reaction on the surface of the bifunctional electrode to generate ammonia, and simultaneously utilizing the hydrogen bonding between the layered structure of molybdenum trioxide in the bifunctional electrode and ammonia to store the generated ammonia in situ on the electrode.
[0043] In some embodiments, the high-valence inorganic nitrogen includes at least one of nitrate, nitrite, nitric oxide, and nitrogen dioxide, with a concentration of 20-500 mg N / L; the applied voltage is 1-8 V, and the reaction time is 2-10 h.
[0044] The application method provided by this invention directly involves immersing a self-supporting layered molybdenum-copper bifunctional electrode as the working electrode into wastewater containing high-valence inorganic nitrogen. After treatment at 1-8 V for 2-10 h, the electrochemical reduction of high-valence inorganic nitrogen to ammonia and the in-situ storage and recovery of ammonia can be achieved simultaneously on the same electrode.
[0045] This method requires no complex reactor structure, is easy to operate, and has low equipment costs. More importantly, the ammonia generated during reduction is immediately captured and stored by molybdenum trioxide on the electrode through hydrogen bonding, avoiding the cumbersome steps of releasing ammonia into the solution phase and then recovering it separately. This fundamentally solves the problems of separation between the reduction and recovery phases, easy secondary pollution caused by ammonia, and low recovery efficiency in traditional processes.
[0046] Experiments show that, after treatment at 5 V for 6 h, the removal rate of nitrate (140 mg N / L) reached 77.9% and the ammonia recovery rate reached 89.2%; the removal rate of nitrite (140 mg N / L) reached 66.1% and the ammonia recovery rate reached 95.8%; the removal rate of total inorganic nitrogen in actual municipal wastewater reached 97.5% and the ammonia recovery rate reached 97.3%. Moreover, the recovered ammonia is enriched on the electrode in the form of high-purity ammonium salt, which can be directly utilized as a resource without further purification.
[0047] To facilitate a further understanding of the present invention by those skilled in the art, the following examples are provided: Example 1 S1. Cut a certain area of foamed nickel (6×6×2cm), clean its surface impurities and oxides with acetone and dilute hydrochloric acid, and then dry it in a vacuum drying oven to obtain sample one; 125 mg of copper sulfate and 12.124 g of ammonium molybdate heptahydrate were dissolved in 1 L of ultrapure water to obtain a copper-molybdenum molar ratio of 140:1. Nickel foam was fixed using a platinum electrode clamp and then subjected to a copper-molybdenum mixed solution at 8 mA / cm². 2 Electrodeposition reaction was carried out at a current density of 10 min. The resulting nickel foam was washed with ultrapure water and then vacuum dried to obtain a material with a blue-black surface, namely the precursor electrode.
[0048] S2. The precursor electrode was heated to 350℃ in a tube furnace with nitrogen as the protective atmosphere (gas flow rate of 10 mL / min) at a heating rate of 5℃ / min, held at that temperature for 120 min, and then cooled to room temperature to obtain sample two, i.e., the bifunctional electrode; and used to carry out experimental research on electrochemical reduction of inorganic nitrogen and storage of NH3.
[0049] like Figure 1 As shown, Sample 1 is a smooth-surfaced nickel foam.
[0050] like Figure 2 As shown, in sample two, layered MoO3 and granular Cu2O are uniformly distributed on the nickel foam.
[0051] like Figure 3 As shown, in sample two, granular Cu₂O is stacked on the surface of layered MoO₃. Elemental content analysis based on energy dispersive spectroscopy shows that the mass ratio of Mo to Cu is 1:1, proving that the prepared bimetallic material has similar proportions of Mo and Cu and exhibits excellent stability.
[0052] like Figure 4 As shown, Sample 2 has infrared peaks similar to those of Sample 3 (Cu-O) and Sample 4 (Mo-O-Mo, Mo=O), further indicating that its main components are MoO3 and Cu2O.
[0053] Using sample 2 as the cathode, experiments 1-6 were conducted respectively: Experiment 1: Using sample 2 as the cathode, an experiment was conducted to electrochemically reduce nitrate to ammonia in a 50 mg N / L nitrate solution. The current density was 0.3 mA / cm². 2 The reaction time is 6 hours.
[0054] Experimental results are as follows Figure 5 As shown, the nitrate removal rate was 98.4%, and the selectivity for ammonium ions was 98.5%.
[0055] Experiment 2: Using sample 2 as the cathode, an experiment was conducted to electrochemically reduce nitrate to ammonia in a 50 mg N / L nitrite solution, with a current density of 0.3 mA / cm². 2 The reaction time is 6 hours.
[0056] Experimental results are as follows Figure 6 As shown, the nitrite removal rate was 99.8%, and the selectivity for ammonium ions was 99.9%.
[0057] Experiment 3: Using sample 2 as the cathode, an experiment was conducted to electrochemically reduce nitrate to ammonia in a 50 mg N / L nitrogen dioxide solution, with a current density of 0.3 mA / cm². 2 The reaction time is 6 hours.
[0058] Experimental results are as follows Figure 7 As shown, the nitrogen dioxide removal rate was 99.5%, and the selectivity for ammonium ions was 98.5%.
[0059] Experiment 4: Using sample 2 as the cathode, an experiment was conducted to electrochemically store ammonia in a 10 mM ammonium sulfate solution at a current density of 0.5 mA / cm². 2 The reaction time is 6 hours.
[0060] Experiment 5: Using sample 2 as the cathode, an experiment was conducted to electrochemically store sodium in a 10 mM sodium sulfate solution at a current density of 0.5 mA / cm². 2 The reaction time is 6 hours.
[0061] Experiment 6: Using sample 2 as the cathode, an experiment was conducted to electrochemically store potassium in a 10 mM potassium sulfate solution at a current density of 0.5 mA / cm². 2 The reaction time is 6 hours.
[0062] The experimental results of Experiments 4-6 are as follows: Figure 8 As shown, the sodium ion removal rate was 20.6%; the potassium ion removal rate was 36.9%; and the ammonium ion removal rate was 98.7%.
[0063] Experiment 7: Using sample 2 as the cathode, a cycle stability experiment was conducted on the electrochemical reduction of nitrate to ammonia in a 50 mg N / L nitrate solution, with a current density of 0.3 mA / cm². 2 The reaction time was 6 hours, and the reaction was repeated 15 times.
[0064] The experimental results of Experiment 7 are as follows Figure 9 As shown, the nitrate removal rate remained above 94.1%, and the selectivity of ammonium ions remained above 81.7%.
[0065] Comparative Example 1 S1. Cut a certain area of foamed nickel (6×6×2cm), clean its surface impurities and oxides with acetone and dilute hydrochloric acid, and then dry it in a vacuum drying oven; Dissolve 125 mg of copper sulfate in 1 L of ultrapure water to obtain a solution with a copper concentration of 50 mg / L; S2. The nickel foam was fixed using a platinum electrode clamp and immersed in a copper sulfate solution at 8 mA / cm². 2 Electrodeposition reaction was carried out at a current density for 10 minutes. The resulting nickel foam was washed with ultrapure water and then vacuum dried to obtain a brownish-brown material.
[0066] Brownish-brown nickel foam was heated to 350 °C in a tube furnace under a protective nitrogen atmosphere (gas flow rate of 10 mL / min) at a heating rate of 5 °C / min, held at that temperature for 120 min, and then cooled to room temperature to obtain sample three.
[0067] Using sample three as the cathode, the following experiments were conducted.
[0068] Experiment 1: Using sample 3 as the cathode, an experiment was conducted to electrochemically reduce nitrate to ammonia in a 50 mg N / L nitrate solution. The current density was 0.3 mA / cm². 2 The reaction time is 6 hours.
[0069] Experiment 2: Using sample 3 as the cathode, an experiment was conducted to electrochemically reduce nitrate to ammonia in a 50 mg N / L nitrite solution, with a current density of 0.3 mA / cm². 2 The reaction time is 6 hours.
[0070] Experiment 3: Using sample 3 as the cathode, an experiment was conducted to electrochemically reduce nitrate to ammonia in a 50 mg N / L nitrogen dioxide solution, with a current density of 0.3 mA / cm². 2 The reaction time is 6 hours.
[0071] Experiment 4: Using sample 3 as the cathode, an experiment was conducted to electrochemically store ammonia in a 10 mM ammonium sulfate solution at a current density of 0.5 mA / cm². 2The reaction time is 6 hours.
[0072] Experiment 5: Using sample 3 as the cathode, an experiment was conducted to electrochemically store sodium in a 10 mM sodium sulfate solution at a current density of 0.5 mA / cm². 2 The reaction time is 6 hours.
[0073] Experiment 6: Using sample 3 as the cathode, an experiment was conducted to electrochemically store potassium in a 10 mM potassium sulfate solution at a current density of 0.5 mA / cm². 2 The reaction time is 6 hours.
[0074] Experimental results are as follows Figures 5-8 As shown, the removal rate of nitrate was 96.3%, and the selectivity of ammonium ions was 59.5%; the removal rate of nitrite was 72.0%, and the selectivity of ammonium ions was 41.5%; the removal rate of nitrogen dioxide was 97.0%, and the selectivity of ammonium ions was 62.7%; the removal rate of sodium ions was 51.8%; the removal rate of potassium ions was 55.2%; and the removal rate of ammonium ions was 94.3%.
[0075] Comparative Example 2 S1. Cut a certain area of foamed nickel (6×6×2 cm), clean its surface impurities and oxides with acetone and dilute hydrochloric acid, and then dry it in a vacuum drying oven. 12.124 g of ammonium molybdate heptahydrate was dissolved in 1 L of ultrapure water to obtain a molybdenum solution with a concentration of 1000 mg / L. S2. The nickel foam was fixed using a platinum electrode clamp and injected into the solution at 8 mA / cm². 2 The current density was used to carry out the electrodeposition reaction, and the deposition time was 10 min. The resulting nickel foam was washed with ultrapure water and then vacuum dried to obtain a material with a blue surface.
[0076] Blue nickel foam was heated to 350°C in a tube furnace under a nitrogen protective atmosphere (gas flow rate of 10 mL / min) at a heating rate of 5 °C / min, held at that temperature for 120 min, and then cooled to room temperature to obtain sample four.
[0077] Using sample four as the cathode, the following experiments were conducted.
[0078] Experiment 1: Using sample 4 as the cathode, an experiment was conducted to electrochemically reduce nitrate to ammonia in a 50 mg N / L nitrate solution. The current density was 0.3 mA / cm². 2 The reaction time is 6 hours.
[0079] Experiment 2: Using sample 4 as the cathode, an experiment was conducted to electrochemically reduce nitrate to ammonia in a 50 mg N / L nitrite solution, with a current density of 0.3 mA / cm². 2The reaction time is 6 hours.
[0080] Experiment 3: Using sample 4 as the cathode, an experiment was conducted to electrochemically reduce nitrate to ammonia in a 50 mg N / L nitrogen dioxide solution, with a current density of 0.3 mA / cm². 2 The reaction time is 6 hours.
[0081] Experiment 4: Using sample 4 as the cathode, an experiment was conducted to electrochemically store ammonia in a 10 mM ammonium sulfate solution at a current density of 0.5 mA / cm². 2 The reaction time is 6 hours.
[0082] Experiment 5: Using sample 4 as the cathode, an experiment was conducted to electrochemically store sodium in a 10 mM sodium sulfate solution at a current density of 0.5 mA / cm². 2 The reaction time is 6 hours.
[0083] Experiment 6: Using sample 4 as the cathode, an experiment was conducted to electrochemically store potassium in a 10 mM potassium sulfate solution at a current density of 0.5 mA / cm². 2 The reaction time is 6 hours.
[0084] Experimental results are as follows Figures 5-8 As shown, the nitrate removal rate was 21.4%, and the selectivity for ammonium ions was 80.1%; the nitrite removal rate was 89.4%, and the selectivity for ammonium ions was 58.9%; the nitrogen dioxide removal rate was 23.4%, and the selectivity for ammonium ions was 82.9%; the sodium ion removal rate was 19.4%; the potassium ion removal rate was 57.0%; and the ammonium ion removal rate was 79.1%.
[0085] Comparative Example 3 Compared to Example 1, this comparative example only adjusted the molar ratio of molybdenum to copper to 460:1, while keeping other conditions unchanged, so that the mass ratio of molybdenum to copper in the prepared bifunctional electrode was 5:1, thus obtaining Sample 5.
[0086] Experiments 1-6 were conducted on sample 5. The results showed that the nitrate removal rate was 63.6%, and the selectivity for ammonium ions was 67.9%; the nitrite removal rate was 85.3%, and the selectivity for ammonium ions was 55.4%; the nitrogen dioxide removal rate was 21.5%, and the selectivity for ammonium ions was 73.5%; the sodium ion removal rate was 23.5%; the potassium ion removal rate was 45.1%; and the ammonium ion removal rate was 85.4%.
[0087] Comparative Example 4 Compared to Example 1, this comparative example only adjusted the molar ratio of molybdenum to copper to 40:1, while keeping other conditions unchanged, so that the mass ratio of molybdenum to copper in the prepared bifunctional electrode was 1:2, resulting in Sample Six.
[0088] Experiments 1-6 were conducted on sample 6. The results were as follows: nitrate removal rate was 97.3%, and ammonium ion selectivity was 76.1%; nitrite removal rate was 75.1%, and ammonium ion selectivity was 65.4%; nitrogen dioxide removal rate was 87.2%, and ammonium ion selectivity was 70.1%; sodium ion removal rate was 45.5%; potassium ion removal rate was 48.7%; and ammonium ion removal rate was 88.6%.
[0089] The above technical solutions of the present invention are merely preferred embodiments of the present invention and do not limit the patent scope of the present invention. All equivalent structural transformations made under the technical concept of the present invention using the contents of the present invention specification and drawings, or direct / indirect applications in other related technical fields, are included in the patent protection scope of the present invention.
Claims
1. A method for fabricating a self-supporting layered molybdenum-copper bifunctional electrode, characterized in that, Including the following steps: The substrate was placed in a molybdenum-copper solution for electro-reduction co-deposition, and molybdenum trioxide and cuprous oxide were deposited in situ on the surface of the substrate to obtain the precursor electrode. The precursor electrode is calcined to obtain a bifunctional electrode. In the bifunctional electrode, the molybdenum trioxide is in the form of nanoribbons, which interweave to form a porous layered structure; the cuprous oxide is distributed in the interlayer and / or surface of the molybdenum trioxide in the form of particles.
2. The method for preparing the self-supporting layered molybdenum-copper bifunctional electrode according to claim 1, characterized in that, The substrate includes at least one of nickel foam, titanium sheet, titanium mesh, nickel sheet, and iron sheet.
3. The method for preparing the self-supporting layered molybdenum-copper bifunctional electrode according to claim 1, characterized in that, The preparation of the molybdenum-copper solution includes: mixing copper salt and molybdenum salt in a solvent to obtain the molybdenum-copper solution; The copper salt includes at least one of copper sulfate, copper chloride, and copper nitrate, and the molybdenum salt includes at least one of sodium molybdate, potassium molybdate, and ammonium molybdate.
4. The method for preparing the self-supporting layered molybdenum-copper bifunctional electrode according to claim 1, characterized in that, The concentration of copper in the molybdenum-copper solution is 10-150 mg / L, and the concentration of molybdenum is 1000-9000 mg / L. The molar ratio of molybdenum to copper in the molybdenum-copper solution is 4.5-600.
5. The method for preparing the self-supporting layered molybdenum-copper bifunctional electrode according to claim 1, characterized in that, The current density for the electroreduction co-deposition is 1-50 mA / cm². 2 The duration is 10-300 minutes.
6. The method for preparing the self-supporting layered molybdenum-copper bifunctional electrode according to claim 1, characterized in that, The calcination treatment is carried out at a temperature of 200-500℃ for a duration of 60-200 min.
7. A self-supporting layered molybdenum-copper bifunctional electrode, characterized in that, Prepared by the preparation method according to any one of claims 1-6, the bifunctional electrode exhibits a porous layered structure with interwoven nanoribbons, comprising layered molybdenum trioxide and granular cuprous oxide, wherein the cuprous oxide is distributed between the layers and / or on the surface of the molybdenum trioxide.
8. The self-supporting layered molybdenum-copper bifunctional electrode according to claim 7, characterized in that, The mass ratio of molybdenum to copper in the bifunctional electrode is 0.9-1.1:0.9-1.
1.
9. The application of the self-supporting layered molybdenum-copper bifunctional electrode prepared by the method according to any one of claims 1-6, or the self-supporting layered molybdenum-copper bifunctional electrode according to claim 7 or 8, in the reduction of high-valence inorganic nitrogen and the recovery of ammonia, characterized in that, include: The self-supporting layered molybdenum-copper bifunctional electrode is placed as the working electrode in wastewater containing high-valence inorganic nitrogen. A voltage is applied to the bifunctional electrode, causing the high-valence inorganic nitrogen to undergo an electrochemical reduction reaction on the surface of the bifunctional electrode to generate ammonia. At the same time, the generated ammonia is stored in situ on the electrode by utilizing the hydrogen bonding between the layered structure of molybdenum trioxide in the bifunctional electrode and ammonia.
10. The application according to claim 9, characterized in that, The high-valence inorganic nitrogen includes at least one of nitrate, nitrite, nitric oxide, and nitrogen dioxide, with a concentration of 20-500 mg N / L; the applied voltage is 1-8 V, and the reaction time is 2-10 h.